Building automation system / Mohd Razif Zainal Abidin ... [et al.] - Zainal Abidin, Mohd Razif; Mastor, Hamzah; Biju, Naong (1989)
A building is a dynamic entity, it has to provide and protect the internal enviroment and the whole range of support activities in a constantly changing scene. For example, the weather and outside enviroment are constantly changing, the occupation and function within the building are constantly changing and also the security and safety measure are constantly changing